The use of ozone technologies in grain storage - Golota, V.I.; Taran, G.V.; Zamuriev, А.А.; Opalev, P.O.; Pugach, S.G.; Mankovskyi, S.N.; Petrenkova, V.P.; Nyska, I.N. (Вопросы атомной науки и техники, 2018)
The results of experimental studies of toxicogenic fungi activity inhibition at various ozone concentration and
doses by ozone-air mixture, which were carried out at the developed and manufactured experimental stand are given. The ozone inhibitory effect on the growth of fungi infection Aspergillus flavus and Penicillium nordicum is defined. The ozone-air mixture ability to limit the mold fungi development on the wheat and barley grains during their
storage is shown. Наведено результати експериментальних досліджень пригнічення озоно-повітряною сумішшю активності токсигенних грибів при різних концентраціях і дозах озону, які проведені на розробленому і виготовленому експериментальному стенді. Визначено ингібіруючий вплив озону на розвиток грибкової інфекції
Aspergillus flavus і Penicillium nordicum. Показана здатність озоно-повітряної суміші пригнічувати розвиток
плісеневих грибів на зерні пшениці і ячменю під час їх зберігання. Приведены результаты экспериментальных исследований подавления озоно-воздушной смесью активности токсигенных грибов при различных концентрациях и дозах озона, которые проведены на разработанном
и изготовленном экспериментальном стенде. Определено ингибирующее воздействие озона на развитие
грибной инфекции Aspergillus flavus и Penicillium nordicum. Показана способность озоно-воздушной смеси
подавлять развитие плесневых грибов на зерне пшеницы и ячменя во время их хранения.